Faktory ovlivňují elasticitu poptávky českého spotřebitele - Luňáček, Jiří; Meluzínová, Jana (Vysoké učení technické v Brně, Fakulta podnikatelská, 2013)
Purpose of the article: The mission of economics in practical application can be described as an additional tool for the deeper understanding of the connection between market subjects. The price elasticity of demand is an extremely important value for the right pricing strategy. In many cases there are merely theoretical concepts, and concrete values for the actual situation are lacking. The objective of this paper is to evaluate methods for identifying demand elasticity. Methodology/methods: The article will compare data from previous studies and discuss possible changes of the coefficients of elasticity for the Czech consumer. Two different procedures will be used for the solution. Reference values will be calculated by a standard approach of correlation and regression analysis. In the next section, these results will be compared with the second procedure, which is more focused on the possible variability of individual responses. The values determined are then compared with known values from the past and from the literature. Scientific aim: The article is based on concepts of elasticity from the theoretical economics. For conclusion will use econometrics modeling. Evaluation and prediction elasticity just for eare of the Czech Republic is innovative. Findings: All items from the research became less elasticity. Values of elasticity for the Czech consumer are nowadays practically the same like the demand elasticity of American consumer. Position of item in the consumer basket is not so important factor like the income of consumer. Conclusions: For the past 9 years, there has been a significant change in the coefficient of elasticity of demand. In 2003, most of the items ranged in values significantly greater than –1. A relevant explanation of this situation may be changing income and the different structure of the consumer basket. As was clear from the first experiment, income influenced elasticity of consumers significantly.
The Factors Influences Elasticity of Demand for the Czech Consumer
Keywords: Elasticity; Demand; Consumer Basket; Regression Analyses; Standard Deviation